A novel low-temperature fabrication approach of composite phase change materials for high temperature thermal energy storage. (1st March 2019) - Yu, Qinghua; Jiang, Zhu; Cong, Lin; Lu, Tiejun; Suleiman, Bilyaminu; Leng, Guanghui; Wu, Zhentao; Ding, Yulong; Li, Yongliang
Graphical abstract: Highlights: A novel route based on cold sintering is set up to fabricate composite materials. Phase change materials were well encapsulated in dense matrix at a low temperature. The composite materials showed stable shape and little leakage after thermal cycling. Excellent mechanical property was obtained at a sintering pressure of over 220 MPa. The resulting composite pellets exhibited decent heat storage performance. Abstract: Phase change materials (PCMs) are generally integrated into matrix materials to form shape-stabilized composite heat storage materials (HSMs) used for high temperature thermal energy storage applications. The conventional fabrication of composite HSMs is prevalently implemented at quite high temperatures, which is energy-intensive and narrows down the range of applicable PCMs because of thermal decomposition. Therefore, this paper establishes a novel fabrication approach to accomplish highly dense matrix to encapsulate PCMs at extremely low temperatures, based on the recently developed cold sintering process. The feasibility of the proposed approach was demonstrated by a case study of NaNO3 /Ca(OH)2 composite HSMs. It was observed that the Ca(OH)2 matrix formed dense microstructure with obvious sintered boundaries and successfully encapsulated NaNO3 as PCM. The HSMs maintained stable macroscopic shape after hundreds of thermal cycles, and exhibited an energy storage efficiency of 59.48%, little leakage of PCM, and good thermal stability. Mechanical tests indicated that the HSMs possessed excellent mechanical properties when the sintering pressure is over 220 MPa. The discharging time of stored heat was presented through infrared thermography, and the heat storage capacity measured for the composite HSMs was over four times as high as those of typical solid storage materials of sensible heat, which demonstrated their excellent heat storage performances. The HSMs can be used in the form of packed bed or parallel channel with multi-layered heat storage, which is beneficial for efficiently utilizing solar heat and improving the performance of current energy storage system. This study therefore provides a novel route for energy-saving and low-carbon fabrication of shape-stabilized composite HSMs.